PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN KOPERASI “PENGAYOMAN” PADA RUMAH TAHANAN NEGARA KELAS II B SUKADANA LAMPUNG TIMUR - Muji Santoso; Susi Sulastri (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
This study aims to determine whether there is an influence of transformational leadership on the performance of employees of the "Protecting" Cooperative at Class II B State Detention House Sukadana, East Lampung. The sample in this study were 11 respondents, data analysis techniques using Simple Linear Regression with regression equations. There is an influence of transformational leadership on the performance of the employees of the Cooperative "Pengayoman" at Class II B Detention House Sukadana, East Lampung. This is based on testing where or equal to 6.948 2.262157 and based on calculations where the significance value is 0,000 from 0.05 so that Ho is rejected and Ha is accepted. The magnitude of the effect of transformational leadership on employee performance is 82.5%. While 17.5% is explained by other variables outside the independent variable or transformational leadership.